On Silence, Creativity and Ethics in Organization Studies - Bigo, Vinca (Organization studies, 2018)
Silence is at once a notoriously difficult and most elusive subject. Management and organization studies depict silence as exclusionary, oppressive, needing to be overcome, and as a strategy to resist oppression. The idea that silence might be cultivated for and not against, stressing positive and enabling (and yet non instrumental) aspects of silence, is meanwhile much less considered. Yet if silence excludes, it can exclude all sorts of things, including undesirable things. Silences forge an emptiness, and so a space for the possible emergence of something new, beyond existing beliefs, norms and practices. Certain silences facilitate creativity, including creativity of an ethical sort. The endeavour of this article is to in part interrogate and deconstruct the current status of silence in management and organization studies, and further to anchor the topic more firmly in organizational scholarship and practice, particularly in relation to ethics and creativity.